Mapping reliability in multicenter MRI: voxel-based morphometry and cortical thickness - Schnack, Hugo G.; van Haren, Neeltje E.M.; Brouwer, Rachel M.; van Baal, G. Caroline M.; Picchioni, Marco; Weisbrod, Matthias; Sauer, Heinrich; Cannon, Tyrone D.; Huttunen, Matti; Lepage, Claude; Collins, D. Louis; Evans, Alan; et al. (Human brain mapping, 2010)
Multicenter structural MRI studies can have greater statistical power than single-center studies. However, across-center differences in contrast sensitivity, spatial uniformity, etc., may lead to tissue classification or image registration differences that could reduce or wholly offset the enhanced statistical power of multicenter data. Prior work has validated volumetric multicenter MRI, but robust methods for assessing reliability and power of multisite analyses with voxel-based morphometry (VBM) and cortical thickness measurement (CORT) are not yet available. We developed quantitative methods to investigate the reproducibility of VBM and CORT to detect group differences and estimate heritability when MRI scans from different scanners running different acquisition protocols in a multicenter setup are included.
Gesehen am 20.06.2023